Early Growth Response 1 Suppresses Macrophage Phagocytosis by Inhibiting NRF2 Activation Through Upregulation of Autophagy During Pseudomonas aeruginosa Infection - Pang, Zheng; Xu, Yan; Zhu, Qingjun (Frontiers in Cellular and Infection Microbiology, 2022)
Pseudomonas aeruginosa is an opportunistic pathogen that causes life-threatening infections in cystic fibrosis patients and immunocompromised individuals. A tightly regulated immune response possessed by healthy individuals can effectively control P. aeruginosa infections, whereas the patients with dysregulated immune response are susceptible to this bacterial pathogen. Early growth response 1 (Egr-1) is a zinc-finger transcription factor involved in regulation of various cellular functions, including immune responses. We previously identified that Egr-1 was deleterious to host in a mouse model of acute P. aeruginosa pneumonia by promoting systemic inflammation and impairing bacterial clearance in lung, which associated with reduced phagocytosis and bactericidal ability of leucocytes, including macrophages and neutrophils. However, the molecular mechanisms underlying the Egr-1-suppressed phagocytosis of P. aeruginosa are incompletely understood. Herein, we investigated whether the Egr-1-regulated autophagy play a role in macrophage phagocytosis during P. aeruginosa infection by overexpression or knockdown of Egr-1. We found that overexpression of Egr-1 inhibited the phagocytic activity of macrophages, and the autophagy activator rapamycin and inhibitor chloroquine could reverse the effects of Egr-1 knockdown and Egr-1 overexpression on phagocytosis of P. aeruginosa, respectively. Furthermore, the Egr-1-overexpressing macrophages displayed upregulated expression of autophagy-related proteins LC3A, LC3B and Atg5, and decreased levels of p62 in macrophages. Further studies revealed that the macrophages with Egr-1 knockdown displayed enhanced activation of transcription factor NRF2 and expression of scavenger receptors MACRO and MSR1. Altogether, these findings suggest that Egr-1 suppresses the phagocytosis of P. aeruginosa by macrophages through upregulation of autophagy and inhibition of NRF2 signaling.